Collapse of density wave and emergence of superconductivity in pressurized-La4Ni3O10 evidenced by ultrafast spectroscopy - Shuxiang Xu; Hao Wang; Mengwu Huo; Deyuan Hu; Qiong Wu; Li Yue; Dong Wu; Meng Wang; Tao Dong; Nanlin Wang (Nature Communications)
Abstract Recent discoveries of superconductivity in Ruddlesden-Popper nickelates realize a rare category of superconductors. However, the use of high-pressure diamond anvil cells limits spectroscopic characterization of the density waves and superconducting gaps. Here, we systematically studied the pressure evolution of La4Ni3O10 using ultrafast optical pump-probe spectroscopy. We found that the transition temperature and energy gap of density waves are suppressed with increasing pressure and disappear suddenly near 17 GPa where structural transition appears. In addition, the observation of a single density wave gap indicates that the spin density wave and charge density wave remain coupled as pressure increases, rather than decoupling. After the density wave collapse, a distinct low-temperature regime emerges, characterized by a small gap consistent with potential superconducting pairing. The separated phase region of superconductivity and density waves suggests that superconductivity in pressurized-La4Ni3O10 competes strongly with density waves, offering new insights into the interplay between these two phenomena.